Repeated-sprint performance and plasma responses following beetroot juice supplementation do not differ between recreational, competitive and elite sprint athletes - Jonvik, K. L.; Nyakayiru, J.; Van Dijk, J. W.; Maase, K.; Ballak, S. B.; Senden, J. M. G.; Van Loon, L. J. C.; Verdijk, L. B. (European Journal of Sport Science, 2018)
Purpose: There is an ongoing debate whether highly trained athletes are less responsive to the ergogenic properties of nitrate. We assessed the effects of nitrate supplementation on plasma nitrate and nitrite concentrations and repeated-sprint performance in recreational, competitive and elite sprint athletes. Methods: In a randomized double-blinded cross-over design, recreational cyclists (n = 20), national talent speed-skaters (n = 22) and Olympic-level track cyclists (n = 10) underwent two 6-day supplementation periods; 140 mL/d nitrate-rich (BR; ~800 mg/d) and nitrate-depleted (PLA; ~0.5 mg/d) beetroot juice. Blood samples were collected and three 30-s Wingate tests were performed. Results: Plasma nitrate and nitrite concentrations were higher following BR vs PLA (P < .001), with no differences between sport levels (all P > .10). Peak power over the three Wingates was not different between BR and PLA (1338 ± 30 vs 1333 ± 30 W; P = .62), and there was no interaction between treatment (BR-PLA) and Wingate number (1-2-3; P = .48). Likewise, mean power did not differ between BR and PLA (P = .86). In contrast, time to peak power improved by ~2.8% following BR vs PLA (P = .007). This improvement in BR vs PLA was not different between Wingate 1, 2 and 3. Moreover, the effects of BR vs PLA did not differ between sport levels for any Wingate parameter (all P > .30). Conclusion: The plasma and repeated-sprint performance responses to beetroot juice supplementation do not differ between recreational, competitive and elite sprint athletes. Beetroot juice supplementation reduces time to reach peak power, which may improve the capacity to accelerate during high-intensity and sprint tasks in recreational as well as elite athletes.